Experiences with An Addiction Consultation Service on Care Provided to Hospitalized Patients with Opioid Use Disorder: A Qualitative Study of Hospitalists, Nurses, Pharmacists, and Social Workers. Issue 1 (December 2022) - Callister, Catherine; Lockhart, Steven; Holtrop, Jodi Summers; Hoover, Kaitlyn; Calcaterra, Susan L.
Background: In response to the opioid epidemic, addiction consultation services (ACS) increasingly provide dedicated hospital-based addiction treatment to patients with substance use disorder. We assessed hospitalist and medical staff perceptions of how the presence of 2 hospitals' ACS impacted care for hospitalized patients with opioid use disorder (OUD). We inquired about ongoing challenges in caring for this patient population. Methods: We conducted a qualitative study of hospital-based providers utilizing focus groups and key informant interviews for data collection. Transcripts were analyzed using a mixed inductive-deductive approach. Emergent themes were identified through an iterative, multidisciplinary team–based process using a directed content analysis approach. Results: Hospitalists ( n  = 20), nurses ( n  = 13), social workers ( n  = 11), and pharmacists ( n  = 18) from a university hospital and a safety-net hospital in Colorado participated in focus groups or key informant interviews. In response to the availability of an ACS, hospitalists described increased confidence using methadone and buprenorphine to treat opioid withdrawal, which they perceived as contributing to improved patient outcomes and greater job satisfaction. Participants expressed concern about inconsistent care provided to patients with OUD that varied by the admitting team's specialty and the physician's background and training. Nurses and hospitalists reported frustrations with achieving adequate pain control among patients with OUD. Last, pharmacists reported practice variations when physicians dosed buprenorphine for acute pain among patients with OUD. A lack of standardized dosing led to concerns of inadequate analgesia or return to opioid use following hospital discharge. Conclusions: An ACS reportedly supports hospitalists and medical staff to best care for hospitalized patients with OUD. Notably, care provided to patients with OUD may not be uniform depending on various physician-level factors. Future work to address the concerns reported by study participants may include education for OUD treatment, early involvement of the ACS, and incorporation of buprenorphine prescribing algorithms to standardize care.